Critical Discourse Analysis in Engineering Education: Developing Critical Technical Literacy Through International Standards Analysis - Ade Irma Khairani; Siti Asnida Nofianna; Nuraini; Winda Syafitri; Ibnu Ajan Hasibuan; Aprima Matondang (Indonesian Technology and Education Journal, 2026)
International technical manuals and standards are commonly taught in engineering education as neutral and factual documents. This study aims to examine how such documents construct authority, obscure agency, and embed ideological assumptions, while also evaluating the effectiveness of a Critical Discourse Analysis (CDA)-based pedagogical module in developing students’ Critical Technical Literacy (CTL). A two-phase mixed-methods design was employed. In Phase 1, systematic CDA was conducted on seven technical documents consisting of four ISO/IEC standards and three corporate manuals from Siemens, Autodesk, and Rockwell Automation using Fairclough’s three-dimensional framework. In Phase 2, a 14-week instructional module was implemented with 87 fourth-year electrical engineering students across three semesters. Data were collected through a validated CTL pre-test and post-test, students’ final analytical assignments, and semi-structured focus group interviews. The CDA results showed that technical documents frequently used passive voice, nominalization, agent deletion, and dominant deontic modality, particularly the word “shall,” to construct authority and reduce visibility of human decision-making. The pedagogical intervention significantly improved students’ CTL scores from pre-test (M = 52.4, SD = 11.7) to post-test (M = 76.8, SD = 9.2), with a large effect size, t(86) = 14.26, p < .001, Cohen’s d = 1.53. The findings suggest that CDA can be integrated into engineering education to strengthen students’ ethical awareness, critical reading ability, and sociotechnical understanding of technical standards. This study contributes an interdisciplinary model that connects critical discourse studies with engineering education and positions CTL as a measurable learning outcome for preparing socially responsible engineers.